Letter from Robert S. Mulliken to Harrison Shull, 1962 - Mulliken, Robert Sanderson (1962)
Letter between Robert S. Mulliken and Harrison Shull, American quantum chemists, concerning the work of Dr. F. A. Matsen on a "machine program for valence bond calculations," as well as program planning for an upcoming conference.
Keywords: Cyanamid European Research Institute; Ions; Shull, Harrison; Biochemists; Intermolecular forces; Intermolecular forces--Computer simulation; Mulliken, Robert Sanderson; Chemists; Quantum chemistry; Nobel Prize winners; Jorgensen, Christopher Klixbull; Physicists; Valence (Theoretical chemistry); Matsen, F.A. (Frederick Albert), 1914-